Comparison of 304 SS, 2205 SS, and 410 SS Corrosion by Sulfate-Reducing Desulfovibrio ferrophilus - Junlei Wang; Hongfang Liu; Pruch Kijkla; Sith Kumseranee; Suchada Punpruk; Magdy El-Said Mohamed; Mazen A. Saleh; Tingyue Gu (Journal of Chemistry)
Three types of stainless steel (304 SS, 410 SS, and 2205 SS) were evaluated for their corrosion behaviors in microbiologically influenced corrosion (MIC) by Desulfovibrio ferrophilus strain IS5, a relatively new and very corrosive sulfate-reducing bacteria (SRB) strain. The incubation lasted for 7 days in enriched artificial seawater at 28°C and the results showed that 410 SS had a rather large weight loss (6.2 mg/cm2) and a maximum pit depth (118 µm), but 2205 SS and 304 SS did not suffer from significant weight loss or pitting. Electrochemical tests indicated that 2205 SS was slightly more resistant to SRB MIC than 304 SS, while 410 SS was far less resistant.